Peptide nucleic acid probes, kit and method for detecting helicobacter pylori and/or clarithromycin resistance profile and applications - Azevedo, N. F. (2011)
The present invention refers to four peptide nucleic acid probes (PNA) for the detection of Helicobacter pylori and/or response analysis of Helicobacter pylori strains to clarithromycin. These probes are based in molecular biology methods, namely fluorescence in situ hybridization (FISH) that are used in H. pylori clarithromycin susceptibility diagnosis in several sample types, including clinical isolates and biopsies. Due to physical and chemical characteristics inherent in its structure, these probes allow a faster and more sensitive hybridization. A second aspect of the present invention is related with the development of a kit where it is possible to use one or several probes described here and the related process of detection or quantification. The purpose of this kit is to identify H. pylori and its response to clarithromycin in clinical samples.